Dental Health Status in 3-5 Year Old Kindergarten Children in Tehran-Iran in 2003 - M. Ghandahari-Motlagh; H. Zeraati (Frontiers in Dentistry, 2005)
Statement of Problem: Assessing oral hygiene in children plays an important role in determining the health status of communities and evaluating national health promotion programs. In 1997 in Geneva, international organizations agreed on the global goal of achieving a minimum of 90% caries free teeth in 5 year old children. Purpose: This study was aimed to assess the oral health status in Iranian children. Materials and Methods: Among kindergarten children residing in the capital of Iran, Tehran, 400 children between the ages of three and five years were randomly selected and participated in this study. Their deciduous teeth were examined and the health index of dmft was determined for each child. The collected data were analyzed using the one-way ANOVA (with Tukey–Kramer multiple comparisons test for Post Hoc test), t test, and chi square test. Results: In this age group, only 48.3% of the children had no tooth decay. This information shows how far we are from accomplishing the aforementioned goal. A significant increase in tooth decay in these children was correlated with neglecting oral and dental hygiene, and also failing to brush the teeth regularly and wash the mouth after consuming sweets (P